Mitochondrial cristae narrowing upon higher 2-oxoglutarate load - Dlasková, Andrea; Špaček, Tomáš; Engstová, Hana; Špačková, Jitka; Schröfel, Adam; Holendová, Blanka; Smolková, Katarína; Plecitá-Hlavatá, Lydie; Ježek, Petr (Biochimica et biophysica acta. Bioenergetics, 2019)
Hypoxia causes mitochondrial cristae widening, enabled by the ~20% degradation of Mic60/mitofilin, with concomitant clustering of the MICOS complex, reflecting the widening of crista junctions (outlets) (Plecitá-Hlavatá et al. FASEB J., 2016 30:1941-1957). Attempting to accelerate metabolism by the addition of membrane-permeant dimethyl-2-oxoglutarate (dm2OG) to HepG2 cells pre-adapted to hypoxia, we found cristae narrowing by transmission electron microscopy. Glycolytic HepG2 cells, which downregulate hypoxic respiration, instantly increased respiration with dm2OG. Changes in intracristal space (ICS) morphology were also revealed by 3D super-resolution microscopy using Eos-conjugated ICS-located lactamase-β. Cristae topology was resolved in detail by focused-ion beam/scanning electron microscopy (FIB/SEM). The spatial relocations of key cristae-shaping proteins were indicated by immunocytochemical stochastic 3D super-resolution microscopy (dSTORM), while analyzing inter-antibody-distance histograms: i) ATP-synthase dimers exhibited a higher fraction of shorter inter-distances between bound F1-α primary Alexa-Fluor-647-conjugated antibodies, indicating cristae narrowing. ii) Mic60/mitofilin clusters (established upon hypoxia) decayed, restoring isotropic random Mic60/mitofilin distribution (a signature of normoxia). iii) outer membrane SAMM50 formed more focused clusters. Less abundant fractions of higher ATP-synthase oligomers of hypoxic samples on blue-native electrophoresis became more abundant fractions at the high dm2OG load and at normoxia. This indicates more labile ATP-synthase dimeric rows established at crista rims upon hypoxia, strengthened at normoxia or dm2OG-substrate load. Hypothetically, the increased Krebs substrate load stimulates the cross-linking/strengthening of rows of ATP-synthase dimers at the crista rims, making them sharper. Crista narrowing ensures a more efficient coupling of proton pumping to ATP synthesis. We demonstrated that cristae morphology changes even within minutes.
Keywords: Mitochondria; Humans; Mitochondrial Proton-Translocating ATPases; buněčné dýchání; dimerizace; Ketoglutaric Acids; Dimerization; Hypoxia; lidé; mitochondrie; Mitochondrial Proteins; mitochondriální protonové ATPasy; mitochondriální proteiny; Hep G2 Cells; kyseliny ketoglutarové; hypoxie; Mitochondrial Membranes; buňky Hep G2; mitochondriální membrány; transmisní elektronová mikroskopie; Microscopy, Electron, Transmission; Cell Respiration